Engineering materials 2 : an introduction to microstructures, processing and design - Ashby, Michael F.; Jones, David R. H., (David Rayner Hunkin), 1945-. (Oxford ; Boston : Butterworth-Heinemann, 1998)
Metals; Ceramics and glasses; Polymers and composites; Designing with metals, ceramics, polymers and composites.
Includes bibliographical references and index.
Keywords: Materials; Materials